IMPLEMENTASI KEBIJAKAN MENGENAI PENGENDALIAN PENGGUNAAN PLASTIK DI KOTA SEMARANG - Indratma Sarwahita; Ari Subowo (Journal of Management and Public Policy, 2026)
The issue of plastic waste in Semarang City has shown a continuous increase along with population growth, economic activities, and the high consumption of single-use plastic products. This condition encouraged the Semarang City Government to establish Mayor Regulation of Semarang City Number 27 of 2019 on the Control of Plastic Use as a policy instrument aimed at reducing plastic waste generation and maintaining environmental balance. This study aims to analyze the implementation of the plastic use control policy in Semarang City and to identify the supporting and inhibiting factors affecting its implementation.This research employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation, with informants selected using purposive sampling. The analysis is based on George C. Edward III’s policy implementation framework, which includes communication, resources, disposition, and bureaucratic structure. The findings indicate that the implementation of Mayor Regulation Number 27 of 2019 has not been fully optimized. The main obstacles include ineffective policy socialization to the public and business actors, limited human resources and supporting facilities, weak consistency in supervision and enforcement of sanctions, and suboptimal coordination among regional government agencies. Nevertheless, several supporting factors were identified, such as the commitment of the local government, the clarity of the regulatory framework, and the increasing awareness of some community members and business actors regarding the importance of reducing plastic use. Based on these findings, this study recommends strengthening continuous and participatory policy socialization, improving the capacity of implementing officials, providing environmentally friendly alternatives to plastic products, and enhancing supervision as well as consistent enforcement of sanctions. These efforts are expected to improve the effectiveness of policy implementation and contribute to achieving environmental balance and sustainable development in Semarang City.